PRAANGGAPAN PADA TUTURAN TOKOH DALAM NOVEL SAMAN KARYA AYU UTAMI DENGAN PERSPEKTIF GENDER (PRESUPPOSITIONS ON THE SPEECH OF CHARACTERS IN AYU UTAMI'S SAMAN NOVEL WITH A GENDER PERSPECTIVE) - M. Syarif Syawwali (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
Presuppositions on the Speech of Characters in Ayu Utami's Saman Novel with a Gender Perspective. This study aims to: 1. describe the presuppositions of the utterances of the characters in the novel Saman, 2. to describe the gender perspective shown in the presuppositions of the utterances of the characters in the novel Saman. This research use desciptive qualitative approach. The appropriate research method is descriptive method. The type of research selected is non-experimental, namely based on literature study. The source of the data in this study is the novel Saman by Ayua Utami and the data in this study are the utterances between characters in the novel Saman and its context which contains presuppositions with a feminist perspective. The process of collecting data in this study used study documentation techniques. Meanwhile, the data analysis technique used is the content study technique. The research instrument is the researcher himself as the key. The results of the research on the analysis of presuppositions of data on the speech of characters in the novel Sam by Ayu Utami have a presupposition category from Yule's theory (in Jumadi, 2006):1. existential presuppositions, 2. lexical presuppositions, 3. factive presuppositions, 4. nonfactive presuppositions, 5. structural presuppositions, and 6. counterfactual presuppositions. Meanwhile, the gender perspective found from the presuppositions are: 1. gender justice and inequality, 2. gender inequality and inequality.Key words: presupposition, feminism, gender, marginalization, subordinationPraanggapan pada Tuturan Tokoh dalam Novel Saman karya Ayu Utami dengan Perspektif Gender. Penelitian ini bertujuan: 1. mendeskripsikan praanggapan pada tuturan tokoh dalam novel Saman, 2. mendeskripsikan perspektif gender yang ditunjukkan dalam praanggapan tuturan tokoh novel Saman. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Metode penelitian yang sesuai adalah metode deskriptif. Jenis penelitian yang dipilih adalah noneksperimen yaitu berdasarkan studi pustaka. Sumber data dalam penelitian ini adalah novel Saman karya AyuaUtami dan data dalam penelitian ini adalah tuturan antartokoh dalam novel Saman beserta dengan konteksnya yang mengandung praanggapan dengan perspektif feminisme. Proses pengumpulan data pada penelitian ini menggunakan teknik studi dokumentasi. Sedangkan, teknik analisis data yang digunakan yaitu teknik kajian isi. Instrument penelitian ini adalah peneliti sendiri sebagai kuncinya. Hasil penelitian terhadap analisis data praanggapan pada tuturan tokoh dalam novel Saman karya Ayu Utami memiliki keenam kategori praanggapan dari teori Yule (dalam Jumadi, 2006, hlm.1). praanggapan eksistensial, 2. praanggapan leksikal, 3. praanggapan faktif, 4. praanggapan nonfaktif, 5. praanggapan struktural, dan 6. praanggapan konterfaktual. Sedangkan, perspektif gender yang ditemukan dari dalam praanggapan berupa: 1. keadilan dan kesetaraan gender, 2. ketidakadilan dan ketidaksetaraan gender.Kata-kata Kunci: praanggapan, feminisme, gender, marginalisasi, subordinasi